IMPLEMENTASI MICROTEACHING BERBASIS METAKOGNISI - Tri Ananda; Dwinasti, Regina; Hijrah Afriani; Riski Ananda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The professional standards of 21st-century elementary education mandate that pre-service teachers possess comprehensive teaching skills integrated with instructional technology. However, conventional microteaching methods often focus narrowly on mechanical lesson plans, causing high procedural anxiety and limited technological adaptability among students. This study aimed to comprehensively investigate the enhancement of pre-service teachers' teaching competence by implementing Technological Pedagogical Content Knowledge (TPACK) learning combined with metacognitive strategies. Employing a Classroom Action Research (CAR) design based on the reflective spiral framework of Kemmis and McTaggart, the research was systematically executed across two consecutive cycles. The subjects comprised elementary school teacher education (PGSD) students enrolled in the mandatory Microteaching course at Universitas Pahlawan Tuanku Tambusai. Empirical data were meticulously gathered using professional basic teaching skills observation sheets, student-constructed TPACK instructional designs, and structured metacognitive self-reflection journals, which were subsequently analyzed via comparative descriptive techniques. The baseline diagnostic evaluation (pre-cycle) revealed that only 20.00% of the students demonstrated acceptable teaching proficiency, primarily due to rigid instructional delivery and an inability to blend technological platforms with content pedagogy. Following the integration of the intervention in Cycle I, teaching competency significantly escalated to 75.00%. Ultimately, in Cycle II, the classical success reached 100.00%, with all students demonstrating exemplary pedagogical performance and high autonomy in executing technology-driven instruction. The application of metacognitive strategies through self-reflection journals empowered students to actively diagnose instructional shortcomings, regulate performance anxieties, and self-correct during peer simulations. This study highly recommends LPTKs to formally embed systematic TPACK-metacognitive frameworks and reflective self-assessment protocols within teacher preparation curriculums to optimize professional educator efficacy.